EDUKASI GIZI KERJA UNTUK PENINGKATAN PRODUKTIVITAS PADA TENAGA KERJA - Anggi Isnani Parinduri; Annisa Febriana Siregar; Raisha Octavariny (JURNAL PENGMAS KESTRA (JPK), 2021)
The level of productivity in the workforce is influenced by various things, one of the things that can affect productivity is nutrient intake. Nutrient intake will produce energy, where the energy produced from food is able to determine health conditions and physical ability to do work. The purpose of implementing community service is to educate the workforce about the importance of nutrition for workers in achieving a good level of productivity and providing leaflets as reading material. This community service was carried out at PT Pelita Adi Pratama, Sei Merbau Village, Tanjung Balai. The implementation of this community service begins with the presentation of the objectives of the activity, then continues with the delivery of material on occupational nutrition education to increase labor productivity. After the delivery of the material is complete, a question and answer session is held to evaluate the success of the activities that have been carried out.